Autism / Mind and Brain - Frith Uta; Hill Elisabeth (Oxford University Press, 2004)
A comprehensive overview of currently conducted experiments, which are guided by bold theories that are being tested rigorously. Introduction, Understanding Autism: Insights from Mind and Brain, A Retrospective Analysis of the Clinical Case Records of ''Autistic Psychopaths'' , Identifying Neurocognitive Phenotypes in Autism, Why is Joint Attention a Pivotal Skill in Autism?, Does the Perception of Moving Eyes Trigger Reflexive Visual Orienting in Autism?, The Pathogenesis of Autism: Insights from Congenital Blindness, The Enactive Mind and or from Actions to Cognition: Lessons from Autism, The Systemizing Quotient: An Investigation of Adults with Asperger Syndrome or High-Functioning Autism and Normal Sex Differences, Towards an Understanding of the Mechanisms of Weak Central Coherence Effects: Experiments in Visual Configural Learning and Auditory Perception, Disentangling Weak Coherence and Executive Dysfunction: Planning Drawing in Autism and Attention-Deficit/ Hyperactivity Disorder, Autism and Movement Disturbance, Index.